Occurrence and Exposure Assessment of Mycotoxins in Ready-to-Eat Tree Nut Products through Ultra-High Performance Liquid Chromatography Coupled with High Resolution Q-Orbitrap Mass Spectrometry - Alfonso Narvaez; Yelko Rodriguez-Carrasco; Luigi Castaldo; Luana Izzo; Giulia Graziani; Alberto Ritieni (Mycotoxins: An Under-evaluated Risk for Human Health, 2022)
Tree nuts have become popular snacks due to their attributed benefits in the health state. Nevertheless, their susceptibility to fungal contamination lead to the occurrence of potentially dangerous mycotoxins. Hence, the aim of this work was to evaluate the presence of mycotoxins in ready-to-eat almonds, walnuts, and pistachios from Italian markets. The most relevant mycotoxin found in almonds was \(α\) -zearalanol in 18% of samples (n = 17) ranging from 3.70 to 4.54 \(μ g/kg\) . Walnut samples showed frequent contamination with alternariol, present in 53% of samples (n = 22) at levels from 0.29 to 1.65 \(μ g/kg\) . Pistachios (n = 15) were the most contaminated commodity, with \(β\) -zearalenol as the most prevalent toxin present in 59% of samples ranging from 0.96 to 8.60 \(μ g/kg\) . In the worst-case scenario, the exposure to zearalenone-derived forms accounted for 15.6% of the tolerable daily intake, whereas it meant 12.4% and 21.2% of the threshold of toxicological concern for alternariol and alternariol monomethyl-ether, respectively. The results highlighted the extensive presence of Alternaria toxins and zearalenone-derived forms, scarcely studied in ready-to-eat tree nut products, highlighting the necessity to include these mycotoxins in analytical methods to perform more realistic risk assessments.